(untitled) (mathematica didactica, 2025)
Whereas data literacy focuses on an individual’s ability to utilize data, statistical literacy focuses on two interlocutor’s ability to interpret and communicate about data-based arguments. The communicative component of statistical literacy, however, remains underdeveloped in research discourse. This contribution illustrates a framework for the communicative component by adapting Habermas’ rationality constructs. The results of an empirical study show that the framework allows deep insights into students’ statistical literacy. This also allows a clearer specification of the relation between data literacy and statistical literacy.